2001
DOI: 10.1007/s007050170128
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the haemagglutinin and the neuraminidase genes prior to the emergence of highly pathogenic H7N1 avian influenza viruses in Italy

Abstract: Outbreaks of avian influenza due to an H7N1 virus of low pathogenicity occurred in domestic poultry in northern Italy from March 1999 until December 1999 when a highly pathogenic avian influenza (HPAI) virus emerged. Nucleotide sequences were determined for the HA1 and the stalk region of the neuraminidase (NA) for viruses from the outbreaks. The HPAI viruses have an unusual multibasic haemagglutinin (HA) cleavage site motif, PEIPKGSRVRRGLF. Phylogenetic analysis showed that the HPAI viruses arose from low pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
219
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 272 publications
(231 citation statements)
references
References 27 publications
6
219
0
2
Order By: Relevance
“…This possibility may provide insight into reported H5N1 outbreaks in Mongolia, Siberian Russia, and Europe that have been linked to migratory birds (10). Previously, it has been shown that LPAI could be transmitted from migratory birds to domestic poultry and subsequently acquire a multibasic amino acid cleavage site and gain virulence (23). However, because precursors of both the genotype V and Z viruses isolated from migratory ducks at Poyang Lake were identified in domestic poultry in southern China (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…This possibility may provide insight into reported H5N1 outbreaks in Mongolia, Siberian Russia, and Europe that have been linked to migratory birds (10). Previously, it has been shown that LPAI could be transmitted from migratory birds to domestic poultry and subsequently acquire a multibasic amino acid cleavage site and gain virulence (23). However, because precursors of both the genotype V and Z viruses isolated from migratory ducks at Poyang Lake were identified in domestic poultry in southern China (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Third, HPAI virus H7N1 A/ostrich/Italy/984/00. This widely used and well-characterized HPAI virus is thought to have emerged from a widespread H7 LPAI precursor virus, and was responsible for outbreaks of HPAI across Northern Italy in 1999 and 2000 (Banks et al, 2001;Capua et al, 2002). This virus had not been formally subjected to an intravenous pathogenicity index test, but by extrapolation from the data available (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…There are four reports where low-pathogenic H5 and H7 viruses, after circulating in poultry for 1 to 9 months, have mutated to highly pathogenic viruses (Banks et al 2001;Horimoto et al 1995;Kawaoka, Naeve and Webster 1984;Senne et al 2002).…”
Section: Molecular Changes In the Low-pathogenic H7n2 Virus Since 1994mentioning
confidence: 99%